Caracterização de polímeros utilizados como detectores de partículas nucleares: Padc (CR-39) e diallyl phthalate (DAP) - Pereira, Luiz Augusto Stuani [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The polymers PADC (CR-39) and DiallylPhthalate (DAP), commonly used as solid state nuclear track detectors (SSNTD), were characterized via optical microscopy and Raman and FT-IR spectroscopies in three process: i) without irradiation; ii) as a function of the fluencyof alpha-particle radiation,to the CR-39 detector, and irradiation by induced nuclear fission, to the PAD detector andiii)as a function of the chemical etching time for each of the detectors. The CR-39 detectors were exposed to irradiation with a 226Ra source. On the other hand, the DAP detectors were exposed to fissionable atoms by induction ofthermal neutrons. To reveal thetracks it was used a standard chemical etching for each of the detectors. As for PADC, the chemical etching is 6.25 N NaOH at 70°C for 400 minutes, and for DAP, 15% KOH, 20% water and 65% ethanol at 60°C with a time range from 20 to 30 minutes. Through gradual chemical etching, i.e., decreasing the chemical etching time sequentially, the aim is to study the structure of the latent track (nano-track) without major physical and chemical changes have occurred in the detector. For this purpose, the detectors were analyzed by optical microscopy and Raman and FT-IR spectroscopy. While optical microscopy provides information about morphological changes, the spectroscopic techniques provide information about physical and chemical molecular structure of the detector...

Os polímeros PADC (CR-39) e Diallyl Phthalate (DAP), comumente utilizados como detectores de traços nucleares no estado sólido (Solid State Nuclear Track Detector, SSNTD), foram caracterizados via microscopia óptica e espectroscopia Raman e FT-IR em três processos: i) sem irradiação; ii) em função da fluência de radiação com partículas alfa, para o detector CR-39, e irradiação por fissão nuclear induzida, para o detector DAP, e iii)em função do tempo de ataque químico para cada detector. Os detectores CR-39 foram expostos à irradiação com uma fonte de 226Ra, atingindo fluências da ordem de 1013 alfas/cm2 . Por outro lado, os do tipo DAP foram expostos a átomos fissionados por indução de nêutrons térmicos, com fluência da ordem de 1014 nêutrons/cm2 . Para a revelação dos traços utilizou-se um ataque químico padrão para cada um dos detectores. Sendo para o PADC, 6,25 N de NaOH a 70ºC durante 400 minutos, e para o DAP, 15% de KOH, 20% de água e 65% de etanol a 60oC durante intervalos de tempo de 2 a 30 minutos. Através de ataques químicos gradativos, ou seja, diminuindo-se o tempo de ataquequímico sequencialmente, o objetivo é estudar a estrutura do traço latente (nano-traço) sem que grandes alterações físico-químicas tenham ocorrido no detector. Para isto, os detectores foram analisados através de microscopia óptica e espectroscopias Raman e FT-IR. Enquanto a microscopia óptica fornece informações sobre alterações morfológicas, as técnicas espectroscópicas fornecem informações físico-químicas da estrutura molecular no detector...
Keywords: Fisica; Polímeros; Espectroscopia Raman; Microscopia; Detectores; Physics